MULTIDISCIPLINARY MANAGEMENT OF AWAKE AND SLEEP BRUXISM: A LITERATURE REVIEW - Aleksandra Karolak,; Jakub Michał Lichoń,; Mateusz Józef Goldyn,; Ewa Wietrzykowska,; Piotr Trojan,; Andrzej Wydrych,; Patryk Pindlowski,; Agata Karasiewicz,; Maja Kuklo,; Marta Kras, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Bruxism is currently understood as a range of jaw muscle activities and teeth contact that occur during sleep and/or wakefulness. Awake bruxism can be distinguished from sleep bruxism based on differences in etiology, comorbidities, and the spectrum of muscle activity and clinical manifestations. Although the exact cause of bruxism remains unclear, it is considered to be multifactorial. This article aims to highlight both awake and bruxism and explore various approaches to their management.Aim of the Study: The aim of this article is to review current knowledge on awake and sleep bruxism and increase awareness of its multidisciplinary management.Materials and Methods: A literature review was conducted using the PubMed and Google Scholar databases. The following keywords were used in various combinations: "bruxism," "awake," "sleep" "management," "treatment," and "oral health." Fourty four relevant articles published between 2001 and 2025 were selected for analysis.Results: The most common current approaches to managing awake and sleep bruxism include occlusal splints, mandibular advancement devices, cognitive-behavioral therapy (CBT), biofeedback therapy, mindfulness techniques, self-awareness and self-regulation strategies, physical therapy (such as physiotherapy, exercise, and dry needling), botulinum toxin injections, and non-steroidal anti-inflammatory drugs (NSAIDs) for pain exacerbation.Conclusion: Bruxism and its associated symptoms can significantly affect patients' quality of life. Early identification and appropriate management can help reduce facial muscle soreness, headaches, and general fatigue and pathological tooth wear.